Handbook of natural colorants [ - Bechtold, Thomas; Mussak, Rita (Wiley series in renewable resources, 2009)
The field of natural colorants is split in different directions between current research and applications, with manufacturers requiring more and more to make their products biobased, through public pressure. Bringing together all aspects of natural dyes, Handbook of Natural Colorants presents important and practical issues in the world of natural colorants, their present position and their potential applications with an emphasis on bioresources. The text provides dyers, textile producers, researchers, color chemists, and others with easy and rapid access to the theory and practice of natural c